2022
DOI: 10.22219/raden.v2i1.20378
|View full text |Cite
|
Sign up to set email alerts
|

How kidneys work? Developing of Android-based Adobe animate media for senior high school students

Abstract: Media is one of the determining factors for learning success which can accommodate student critical thinking. Moreover, during the COVID-19 pandemic, learning media became crucial in online learning. This study aims to produce and test the feasibility of android-based media on kidney material developed through Adobe Animate CC software. In addition, it also to find the effectiveness of the media in improving the critical thinking skills of eleventh graders students when used in online learning. Borg & Gall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Education is the main vehicle for preparing quality human resources (Adam, 2022;Agustini et al, 2021;Arifin et al, 2021;Muhlasin et al, 2022;Muninda et al, 2021;Octaviana et al, 2021;Prasetyo et al, 2022;Rohmania et al, 2022;Sari et al, 2021;Varisa & Fikri, 2022), including in preparing careers according to the wishes and aspirations of children. Activities related to career information services can be carried out in various ways, one of them is through career day activities (Muriyawati & Rohmah, 2016).…”
Section: Article Historymentioning
confidence: 99%
“…Education is the main vehicle for preparing quality human resources (Adam, 2022;Agustini et al, 2021;Arifin et al, 2021;Muhlasin et al, 2022;Muninda et al, 2021;Octaviana et al, 2021;Prasetyo et al, 2022;Rohmania et al, 2022;Sari et al, 2021;Varisa & Fikri, 2022), including in preparing careers according to the wishes and aspirations of children. Activities related to career information services can be carried out in various ways, one of them is through career day activities (Muriyawati & Rohmah, 2016).…”
Section: Article Historymentioning
confidence: 99%
“…While, the reproductive system material requires learning media to improve students' understanding and learning outcomes. Learning media is necessary for delivering this material as it involves internal body processes that cannot be directly observed, which makes it challenging for students (Agustini et al, 2021;Ardi et al, 2023;Astatin & Nurcahyo, 2016;Muninda et al, 2021;Prasetyo et al, 2022;Puspita et al, 2017;Syamsurizal et al, 2021). Various studies have shown the effectiveness of different learning media in enhancing students' cognitive learning outcomes in biology subjects related to the reproductive system (Eliana et al, 2022;Ibrahim, 2023;Kurniawan et al, 2018;Panjaitan et al, 2020;Roihana et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Pandemic has generated various problems, ranging from pedagogical and psychological components to technical issues of connectivity (Abriata, 2022). Regardless, science learning with unique characteristics should be learned thru mindon and hands-on (Adam, 2022;Arifin et al, 2022;Ermila et al, 2022;Muhlasin et al, 2022;Nur et al, 2022;Nurhayatus et al, 2022;Prasetyo et al, 2022;Varisa & Fikri, 2022). Hence, teachers should be able to create 2 / 26 virtual, blended, and face-to-face classroom conditions that assist the students to maintain learning momentum even in crisis conditions (Wisanti et al, 2021).…”
Section: Introductionmentioning
confidence: 99%